Pathogenesis of Henoch-Schönlein purpura nephritis - Lau, Keith K. (Springer Berlin Heidelberg, 2010)
The severity of renal involvement is the major factor determining the long-term outcome of children with Henoch-Schönlein purpura (HSP) nephritis (HSPN). Approximately 40% children with HSP develop nephritis, usually within 4 to 6 weeks after the initial onset of the typical purpuric rashes. Although the pathogenetic mechanisms are still not fully delineated, several studies suggest that galactose-deficient IgA1 (Gd-IgA1) is recognized by anti-glycan antibodies, leading to the formation of the circulating immune complexes and their mesangial deposition that induce renal injury in HSPN.